2023
DOI: 10.1111/dar.13606
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sharing equipment among people who inject drugs: The role of community attachment in harm reduction and health promotion

Abstract: Introduction Sharing injecting equipment is a major route of transmission for blood borne viruses such as hepatitis C and HIV. Although needle and syringe programs are widely available throughout metropolitan Australia, rates of sharing equipment have not significantly changed in recent years. This study aimed to identify factors associated with recent equipment sharing among people who inject drugs in Australia. Methods A paper‐based survey was distributed via peer‐based organisations between June and Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…34 Continuing to reduce stigma and discrimination relating to injecting drug use in the community and healthcare settings needs to be a priority for HCV elimination. Other studies reporting on experiences of stigma, such as Broady et al, 35 who found similar levels of injecting drug use related stigma among 731 PWID in 2021 to participants in our study who were 'not engaged in treatment'. 35 Previous analysis using the EC-experience cohort data set by Djordjevic et al 9 identified that higher service use access was associated with greater experiences of stigma among PWID.…”
Section: Open Accesssupporting
confidence: 78%
See 1 more Smart Citation
“…34 Continuing to reduce stigma and discrimination relating to injecting drug use in the community and healthcare settings needs to be a priority for HCV elimination. Other studies reporting on experiences of stigma, such as Broady et al, 35 who found similar levels of injecting drug use related stigma among 731 PWID in 2021 to participants in our study who were 'not engaged in treatment'. 35 Previous analysis using the EC-experience cohort data set by Djordjevic et al 9 identified that higher service use access was associated with greater experiences of stigma among PWID.…”
Section: Open Accesssupporting
confidence: 78%
“…Other studies reporting on experiences of stigma, such as Broady et al, 35 who found similar levels of injecting drug use related stigma among 731 PWID in 2021 to participants in our study who were 'not engaged in treatment'. 35 Previous analysis using the EC-experience cohort data set by Djordjevic et al 9 identified that higher service use access was associated with greater experiences of stigma among PWID. 9 To address these concerns, efforts designed to build trust between patient/providers, including sensitivity training for providers around injecting drug use and understanding competing priorities for this population group, and potentially incentivising providers to treat PWID either through direct payments 36 or providing revised Medical Benefits Schedule (MBS) payments for longer clinic appointments acknowledging the complex needs of these clients.…”
Section: Open Accesssupporting
confidence: 78%
“…However, health professionals also documented negative attitudes and stigma, either because they expressed them themselves or because they identified them in colleagues. The principal ways of discrimination were the intention of not wanting to care for PLWH, the disclosure without consent of patients' serological status, the irrational use of infection control measures, patient avoidance, verbal abuse, physical abuse, and referral were pointed out as unnecessary to other healthcare professional [27,30,36,39,40].…”
Section: N Discussionmentioning
confidence: 99%
“…12% (n=14) witnessed PLWH being subjected to verbal or physical abuse [25]. Also, another manuscript reported that up to 40.4% of professionals had witnessed undignified treatment towards PLWH [39]. According to Krishnaratne et al, health workers who perceived that their coworkers spoke severely about their patients or treated them poorly were more likely to hold critical and stigmatizing attitudes (p<0.01) [36].…”
Section: Stigma On the Part Of Healthcare Professionalsmentioning
confidence: 99%
“…Stigma is consistently endorsed as a barrier to treatment, although few studies have tied it directly to treatment-seeking behavior (Hammarlund et al, 2018). That said, recent stigma monitoring in Australia by Broady et al (2022) found that stigma influenced the health-seeking behaviors of people who inject drugs (PWID) and that many PWID reported receiving negative treatment by health workers. Social stigma can have other treatment implications too, including limiting access to effective treatments, like MOUD.…”
Section: Social Stigma As a Barrier To Opioid Treatment And Recoverymentioning
confidence: 99%